Survey of Device Calibration Techniques for Fingerprinting Localization Algorithms - Juraj Machaj; Peter Brida (Communications - Scientific letters of the University of Zilina, 2013)
In the paper device calibration algorithms for indoor positioning systems based on fingerprinting localization framework are discussed and compared. Device calibration should play important role in development of localization systems based on Wi-Fi since heterogeneous devices have different receiver parameters. This fact causes that the positioning system cannot provide position estimates with sufficient accuracy. In this paper different calibration approaches will be described and two state of art automatic calibration techniques will be compared in the simulations.